Between Post- and Conflict: Ancestral Authority and Political Aggressions in Guatemala's Ixil Region - Michele Grandi (Confluenze)
This article examines the prolonged post-conflict dynamics in Guatemala's Ixil region, focusing on the 2022 assault on the Alcaldía Indígena of Nebaj. Through an ethnographic lens, it highlights how neoliberal decentralization, multicultural reforms, and the legacies of the civil war have reshaped local governance, intertwining historical and global dimensions. Anchored in the remnants of war, the post-conflict period emerges as a space of contestation and experimentation with new forms of autonomy and governance.